The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4184/asj.2011.5.3.155
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Titanium Mesh Cages in the Reconstruction of Anterior Column Defects in Active Spinal Infections: Can We Rest the Crest?

Abstract: Study DesignRetrospective clinical series.PurposeTo assess whether titanium cages are an effective alternative to tricortical iliac crest bone graft for anterior column reconstruction in patients with active pyogenic and tuberculous spondylodiscitis.Overview of LiteratureThe use of metal cages for anterior column reconstruction in patients with active spinal infections, though described, is not without controversy.MethodsSeventy patients with either tuberculous or pyogenic vertebral osteomyelitis underwent a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
1
38
1
5
Order By: Relevance
“…The 10-year rate of spinal fusion using spinal instrumentation is 97 % compared to 90 % with debridement alone; the respective rate of conservative treatment with antibiotics alone ranges from 65 to 79 % [12,15,16,[41][42][43]. However, there is still controversy regarding the use of spinal instrumentation and infection recurrence rates in patients with spondylodiscitis [12,15,16,41].…”
Section: Discussionmentioning
confidence: 94%
“…The 10-year rate of spinal fusion using spinal instrumentation is 97 % compared to 90 % with debridement alone; the respective rate of conservative treatment with antibiotics alone ranges from 65 to 79 % [12,15,16,[41][42][43]. However, there is still controversy regarding the use of spinal instrumentation and infection recurrence rates in patients with spondylodiscitis [12,15,16,41].…”
Section: Discussionmentioning
confidence: 94%
“…Sundararaj et al concluded that titanium cages may be safely used in place of iliac crest graft for treating active spinal infection. Their series included cases of tuberculosis as well as pyogenic spondylodiscitis [14]. Brase et al, in their review of nine prospective cases of purulent spondylodiscitis including cervical and lumbar infections, showed satisfactory clearance of infection with the use of polyetheretherketone (PEEK) cages [22].…”
Section: Discussionmentioning
confidence: 98%
“…Tubercle bacilli have reduced propensity to form biofilm, and thus risk of recurrences with titanium implants is low [11,[14][15][16]. A posterior approach allows for a single-stage surgical procedure, offering satisfactory lesion debridement and simultaneous placement of instrumentation to provide stability and deformity correction, which is well maintained [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For complete debridement, the foci should neither undergo over excision of normal bone, nor overlook infected material that could cause the disease to recur [20]. For the procedure of intervertebral focal graft union, the best graft is autologous iliac bone followed by titanium mesh cage filled with autologous iliac bone [21]. The drawback of the former is chronic pain and cosmetic defect while the latter can undergo mesh subsidence [14].…”
Section: Discussionmentioning
confidence: 99%